Hugh Davies’s Electronic Music Documentation 1961–1968. - Mooney, James (Organised Sound, 2015)
This paper provides an account and interpretation of Hugh Davies’s electronic music research and documentation from the period 1961–1968. It is argued that Davies, particularly via his International Electronic Music Catalog (published 1968), characterised electronic music for the first time as a truly international, interdisciplinary praxis, whereas in the preceding literature the full extent of that international, interdisciplinary scope had been represented only partially, and in a way that was heavily biased in favour of the ostensibly ‘main’ Western European and North American schools. This argument is demonstrated by referring to a range of published sources dating from 1952 to 1962, which represented the praxis of electronic music as somewhat fragmented and parochial, and to a range of Davies’s published and unpublished writings, which conveyed a sense of the various international, aesthetic and disciplinary threads coalescing into an apparently coherent whole. An interpretation of Davies’s motivations for representing electronic music in this way is provided, which has to do with his belief in international and interdisciplinary exchange as catalysts for the development of the electronic idiom. Many subsequent publications rely upon the data provided in the Catalog, which continues to be, arguably, the most complete record of international, interdisciplinary electronic music activity up to the end of 1967. Some examples are given that illustrate the influence of the Catalog upon subsequent studies. It is concluded that further work is needed in order to fully understand and evaluate the historiographic consequences of the Catalog’s influence upon discourses of electronic music history.